New method for combining the channel coding with polar coding-based encryption - Kenarkouhi, Mohammad; Tavakoli, Hassan (Journal of Advanced Computer Science & Technology, 2015)
In this paper, polar codes recently presented by Arikan are introduced. Polar codes have a number of channels with high capacity where information is located. In addition, these codes are composed of a number of channels with low capacity called frozen bits. In the first proposed design, we optimally use frozen and useless bits of the polar code and insert the encryption key on all the bits of the design (information bits and frozen bits). In fact, in Arkian’s proposed 8-bit design, we use 8 encryption keys. Then, in the rest of the article, a method is presented through which the number of encryption keys applied can be reduced. Because, the encryption system is effective and desired in which in addition to the high complexity and the lack of correlation between bits, the minimum number of encryption keys are used.